The vulnerable vessel - Gleißner, C. A. (Hämostaseologie, 2015)
Diabetes represents one of the most important risk factors for atherosclerosis, which is the leading cause of mortality worldwide. Recent imaging studies employing intravascular ultrasound or computed coronary angio - graphy tomography clearly confirm that diabetes is associated with larger plaque burden and with more lesions displaying features of instability. Various molecular mechanisms promoting atherogenesis and plaque destabilization in diabetics have been described in the past. The current review specifically focuses on recent papers that have addressed the effects of diabetes and hyperglycemia (i) on myeloid cells, (ii) on oxidative stress, and (iii) on protein kinase C (PKC) activation. Thus, it has been demonstrated that hyperglycemia may promote myelopoiesis and differentiation of pro-inflammatory macrophages. Furthermore, novel studies emphasize the interplay between inflammation and oxidative stress at both the molecular and the genetic level. Finally, experimental studies shed light on the role of PKC-_ in diabetes-associated atherosclerosis. Several of these recent studies suggest that atherogenesis and plaque destabilization in diabetic individuals may be mediated by diabetes-specific mechanisms. This may open the door for developing tailored anti-atherosclerotic therapies for diabetic patients.
Keywords: Diabetes mellitus; atherosclerosis; protein kinase C